2021
DOI: 10.1016/j.pmedr.2021.101516
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of flu vaccine uptake among racial/ethnic minorities in the United States

Abstract: Research on the social determinants of vaccine uptake often occur between racial/ethnic groups and not within groups. Though minoritized individuals face inequalities across the board, these are also not evenly distributed amongst minoritized individuals within groups. Using the National Health Interview Survey data, we examined disparities in flu vaccine uptake across racial/ethnic groups in the United States (US). We examined (a) NH (non-Hispanic) White (n = 32,655), (b) NH Asian (n = 2335), (c) NH African A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(50 reference statements)
1
5
0
Order By: Relevance
“…Similarly, a recent study highlighted that only 36% of non-Hispanic Black adults accepted influenza vaccination for themselves, compared to 47% of white adults, and those without insurance had a lower odds of receiving the influenza vaccine. [14] We also found that influenza seasons during the COVID-19 pandemic were associated with a lower odds of receiving the influenza vaccine, compared to the season prior to the pandemic. This was even seen among the cohort of patients who had received the influenza vaccine in the year prior to the pandemic.…”
Section: Discussionsupporting
confidence: 51%
“…Similarly, a recent study highlighted that only 36% of non-Hispanic Black adults accepted influenza vaccination for themselves, compared to 47% of white adults, and those without insurance had a lower odds of receiving the influenza vaccine. [14] We also found that influenza seasons during the COVID-19 pandemic were associated with a lower odds of receiving the influenza vaccine, compared to the season prior to the pandemic. This was even seen among the cohort of patients who had received the influenza vaccine in the year prior to the pandemic.…”
Section: Discussionsupporting
confidence: 51%
“…The objective of our empirical work is to evaluate the sources of under-vaccination during the COVID-19 pandemic. In light of the existing literature that emphasizes the role of socioeconomic and demographic factors [ 6 , 7 , 8 , 10 , 11 , 12 , 13 ], we consider the various components that make up the U.S. Centers for Disease Control and Prevention’s [ 26 ] Social Vulnerability Index (SVI). The SVI is aimed at helping public health officials and policymakers better prepare for disease outbreaks and other disasters.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies on the sources of unwillingness to vaccinate draw inferences from cross-sectional survey data. The consensus points to a higher hesitancy among the less-educated, females, racial/ethnic minorities, people living in rural areas, and those with lower income or economic security [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. In the United States, the economically disadvantaged population is predominantly Hispanic or Black.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The similarity noted in the study above and the current study could be due to similarity in socio-demographic variables. Several studies have shown higher hesitancy among those with lower socio-economic class [ 48 , 52 58 ].…”
Section: Discussionmentioning
confidence: 99%